Mother, Infant, and Household Factors Associated with the Type of Food Infants Receive in Developing Countries - Benjamin eYarnoff; Benjamin Todd Allaire; Patrick eDetzel (Frontiers Media S.A., 2014)
Objectives: We explore the complex factors associated with infant feeding by analyzing what mother, infant, and household factors are associated with the types of food given to infants. We seek to quantify associations in order to inform public health policy about the importance of target populations for infant feeding programs. Methods: We used data from the Demographic Health Survey in 20 developing countries for multiple years to examine mother, infant, and household factors associated with six types of food given to infants (exclusive breastfeeding, non-exclusive breastfeeding, infant formula, milk liquids, non-milk liquids, and solid foods). We performed a seemingly unrelated regressions analysis with community-year fixed effects to account for correlation between food types and control for confounding factors associated with community resources, culture, time period, and geography in the pooled analysis. Results: We found that several mother, infant, and household characteristics were associated with each of the feeding types. Most notably, mother's education, working status, and weight are significantly associated with the type of food given to infants. We provide quantified estimates of the association of each of these variables with six types of food given to infants. Conclusions: By identifying maternal characteristics associated with infant feeding and quantifying those associations, we help public health policymakers generate priorities for targeting infant feeding programs to specific populations that are at greatest risk. Higher educated, working mothers are best to target with exclusive breastfeeding programs for young infants. Mothers with lower education are best to target with complementary feeding programs in infants older than 1 year. Finally, while maternal weight is associated with higher levels of exclusive breastfeeding the association is too weak to merit targeting of breastfeeding programs to low-weight mothers.